Mediation of Criminal Cases as an Effort to Settle Criminal Actions Based on Local Wisdom in Indonesia - Budisetyowati, Dwi Andayani; Joko Sriwidodo; Rr. Dijan Widijowati; Juanda (Journal of Law, Politic and Humanities, 2023)
Penal mediation is carried out to bring together criminal offenders and victims, so this penal mediation is often also known as "Victim Offender Mediation" (VOM). In Indonesia itself, the use of mediation can be seen in Law No. 30 of 1999 concerning Arbitration and Dispute Resolution. Settlement of cases through mediation is in line with the concept of local wisdom that lives in Indonesian society. The noble values contained in the Pancasila state foundation fade with the times and technology; the values contained therein, such as divinity, justice, decency, harmony, unity, humanity, and mutual cooperation, are no longer reflected in the lives of the nation, state, and society. Society is also included in the formulation of legal products. Penal mediation is less well known among Indonesians. In mediation, the urgency is the value of Pancasila in the settlement of criminal cases in Indonesia, which is the community's need for a progressive, humane criminal dispute settlement that provides a sense of justice for victims, society, and perpetrators, which cannot be carried out by national criminal law. The local wisdom of people in various regions of Indonesia in the settlement of criminal disputes based on deliberation and consensus (mediation) as local institutions has not been utilized optimally in answering this problem. The formation of law in Indonesia is based on historical aspects and is in accordance with the conditions and circumstances of the people. In mediation, it requires the involvement of all stakeholders in solving criminal acts through mediation based on local wisdom using impartial or neutral media and mediators.